Tissue-specific expression of telomerase reverse transcriptase gene variants in Nicotiana tabacum - Jurečková, Jana Fišerová; Sýkorová, Eva; Hafidh, Said; Honys, David; Fajkus, Jiří; Fojtová, Miloslava (Planta, 2017)
In tobacco, three sequence variants of the TERT gene have been described. We revealed unbalanced levels of TERT variant transcripts in vegetative tobacco tissues and enhanced TERT transcription and telomerase activity in reproductive tissues. Telomerase is a ribonucleoprotein complex responsible for the maintenance of telomeres, structures delimiting ends of linear eukaryotic chromosomes. In the Nicotiana tabacum (tobacco) allotetraploid plant, three sequence variants (paralogs) of the gene coding for the telomerase reverse transcriptase subunit (TERT) have been described, two of them derived from the maternal N. sylvestris genome (TERT_Cs, TERT_D) and one originated from the N. tomentosiformis paternal genome (TERT_Ct). In this work, we analyzed the transcription of TERT variants in correlation with telomerase activity in tobacco tissues. High and approximately comparable levels of TERT_Ct and TERT_Cs transcripts were detected in seedlings, roots, flower buds and leaves, while the transcript of the TERT_D variant was markedly underrepresented. Similarly, in N. sylvestris tissues, TERT_Cs transcript significantly predominated. A specific pattern of TERT transcripts was found in samples of tobacco pollen with the TERT_Cs variant clearly dominating particularly at the early stage of pollen development. Detailed analysis of TERT_C variants representation in functionally distinct fractions of pollen transcriptome revealed their prevalence in large ribonucleoprotein particles encompassing translationally silent mRNA; only a minority of TERT_Ct and TERT_Cs transcripts were localized in actively translated polysomes. Histones of the TERT_C chromatin were decorated predominantly with the euchromatin-specific epigenetic modification in both telomerase-positive and telomerase-negative tobacco tissues. We conclude that the existence and transcription pattern of tobacco TERT paralogs represents an interesting phenomenon and our results indicate its functional significance. Nicotiana species have again proved to be appropriate and useful model plants in telomere biology studies.
Keywords: Euchromatin; orgánová specificita; posttranslační úpravy proteinů; Chromatin Immunoprecipitation; polyribozomy; Telomerase; chromatinová imunoprecipitace; euchromatin; pylová láčka; Transcription, Genetic; Nicotiana; telomerasa; Cell Nucleus; Polyribosomes; Telomere; messenger RNA; Protein Processing, Post-Translational; Genetic Variation; RNA, Messenger; buněčné jádro; Pollen Tube; genetická transkripce; Gene Expression Regulation, Plant; regulace genové exprese u rostlin; Polyploids; Pollen; Organ Specificity; histony; Histones; genetická variace; tabák; Transcription; Gene sequence variant